2010
DOI: 10.1080/00071668.2010.508487
|View full text |Cite
|
Sign up to set email alerts
|

Number of flocks on the same litter and carcase condemnations due to cellulitis, arthritis and contact foot-pad dermatitis in broilers

Abstract: 1. This study was conducted to verify the impact of different kinds of material and the number of times of litter reuse on the incidence of chicken pathologies. Approximately 4·5 million broilers from conventional Brazilian farms were evaluated in the abattoir for cellulitis, arthritis and contact foot-pad dermatitis. 2. Four different kinds of litter material, Brachiaria grass, corncob, sawdust and rice shell, were used. Brachiaria grass litter showed the highest incidence of contact foot-pad dermatitis. Corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…There are no data in the literature about the connection between dermatitis and the use of corncob and wood shavings bedding materials for laboratory animals. However, some researchers have shown that using corncobs and sawdust as bedding materials for broilers is associated with dermatitis and that corncob has a more drastic effect on skin than sawdust (Xavier et al 2010 ). Furthermore, in this study, changing bedding once weekly for both the wood shavings and corncob bedding groups resulted in mild degenerative and inflammatory reactions, while changing bedding twice weekly caused more severe skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data in the literature about the connection between dermatitis and the use of corncob and wood shavings bedding materials for laboratory animals. However, some researchers have shown that using corncobs and sawdust as bedding materials for broilers is associated with dermatitis and that corncob has a more drastic effect on skin than sawdust (Xavier et al 2010 ). Furthermore, in this study, changing bedding once weekly for both the wood shavings and corncob bedding groups resulted in mild degenerative and inflammatory reactions, while changing bedding twice weekly caused more severe skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Cellulitis in chickens occurs with frequencies estimated to range between 0.197% and 6.04% (Schrader et al, 2004). The development of this infection is associated with skin surface injuries, often caused by close contact among birds and litter quality (Xavier et al, 2010). Cellulitis has been successfully reproduced in laboratory chicken models, by subcutaneous injection and by contaminating dermal scratches (Norton et al, 1997).…”
Section: Cellulitismentioning
confidence: 99%
“…Contrary to Europe, where litter is replaced after every flock, the US broiler and broiler breeder industry reuses litter for successive flocks [ 13 , 15 ]. This could be another factor impacting the litter condition and, in turn, poses a risk for contact dermatitis when compared to fresh litter.…”
Section: Introductionmentioning
confidence: 99%